Implementation of the transradial approach as an alternative vascular access for transcatheter aortic valve replacement guidance: Experience from a high‐volume center. Issue 7 (10th December 2018) - Fernandez‐Lopez, Leticia; Chevalier, Bernard; Lefèvre, Thierry; Spaziano, Marco; Unterseeh, Thierry; Champagne, Stéphane; Benamer, Hakim; Sanguineti, Francesca; Garot, Philippe; Hovasse, Thomas
Abstract: Objective: This study sought to assess the potential benefits of the transradial approach (TRA) as an alternative vascular access to the classical contralateral femoral approach for transcatheter aortic valve replacement (TAVR). Background: Vascular and bleeding complications in TAVR have gradually decreased owing to operator experience and downsizing of the delivery system. However, about 1/4 of vascular access site complications are related to the transfemoral (TF) secondary access. Methods: We compared the outcomes at 30 days according to VARC‐2 after TAVR of a prospective cohort of 217 consecutive patients undergoing right or left TRA as the second vascular access (TRA‐TF TAVR) and a retrospective cohort of 194 consecutive patients undergoing TF approach as a second vascular access (TF‐TF TAVR). Results: Baseline clinical characteristics and risk scores were well matched in both groups. Procedural success rate was 99.7%. Fluoro time was significantly lower in the TF‐TF TAVR group (16.9 ± 7.2 vs. 19.1 ± 7.8 min, P = 0.003); however, there was no significant difference in x‐ray exposure, procedure time or amount of contrast used. In the TRA‐TF TAVR group, there were no complications related to the TRA access and there were less vascular and bleeding complications (18.0% vs. 9.7%, P = 0.014; 17.0% vs. 9.2%, P = 0.026, respectively), although blood transfusion requirement or hospitalization duration stay were similar in both groups. Conclusions: TRA approach as alternative secondary vascular access in TAVR is safe and feasible and is associated with a significant decrease in vascular and bleeding complications. Further, large‐scale studies are warranted to confirm the potential benefit of this approach.